Peran Perpustakaan Daerah Kabupaten Karo Dalam Pemanfaatan Program Literasi Inklusi Sosial - Teguh Budimanta Tarigan; Abdul Karim Batubara (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The existence of social inclusion-based regional libraries is a regional library that helps develop community potential by improving the quality of library services in order to foster a successful and enlightened society. Regional library services must now be more proactive in inviting the public to use libraries, so that famous libraries are more than just lending and returning books. As a result, library services can be transformed by social inclusion. The purpose of this paper is to optimize libraries in order to provide individuals with the means to improve their quality of life. This study used qualitative methodology for data collection, including interviews, observations, and documentation in the regional library of Karo Regency. After collecting the data, it is evaluated by reducing the data, presenting the data, and coming up with conclusions. The findings of this study show that the Karo regional library has been able to transform its library services through the use of literacy programs aimed at encouraging social inclusion. It seems that the Karo regional library service has been transformed into a library with flexible services based on people's information needs, as evidenced by the implementation of a number of social inclusion services.